Alcohol-involved overdose deaths in US veterans. (1st January 2022) - Lin, Lewei A.; Bonar, Erin E.; Zhang, Lan; Girard, Rachel; Coughlin, Lara N.
Abstract: Background: Alcohol-involved overdose deaths are increasing and often occur with other substances but have been minimally studied compared to other causes of overdose. Methods: We used national Veterans Health Administration (VHA) records linked to National Death Index data from 2012 to 2018 to examine trends in alcohol-related overdose mortality. Patient characteristics and treatment receipt were compared across categories of alcohol overdose deaths (alcohol-only, alcohol+opioids which may include additional substances, and alcohol+other substances without opioids). Results: From 2012–2018, 2421 Veterans died from an alcohol-involved overdose (alcohol-only: 868, alcohol+opioids: 1269, alcohol+other substances: 284). The alcohol-involved overdose rate increased 57% during this period. Compared to those who died of an alcohol-only overdose, Veterans who died from alcohol+opioids and alcohol+other substances were more likely Black or Hispanic, and to have an opioid use disorder, but less likely to live in rural areas or to be diagnosed with alcohol use disorder (AUD). Only 32.5% of those who died from alcohol-involved overdose received treatment in a substance use disorder clinic in the year preceding death, compared to 65.1% seen in mental health and 85.7% in primary care. Only 9.5% of Veterans who died from alcohol overdose received medication treatment for AUD and 24.8% received psychotherapy for AUD in the year preceding death. Conclusions: Alcohol overdose is increasing primarily related to overdoses involving opioids and other substances. Most patients did not receive any effective medication or psychotherapy treatments for AUD, suggesting further need to identify those at risk and to target treatment for this vulnerable group in healthcare settings. Highlights: Alcohol overdose mortality rate increased 57% in Veterans from 2012 to 2018. Alcohol overdose is increasing primarily due to overdoses involving opioids and other substances. < 10% who died from alcohol overdose received AUD medication and < 25% received psychotherapy. Most Veterans who died from alcohol overdose were seen in primary care or mental health but not in SUD settings.